Pengaruh Ruang Simpan, Media Simpan dan Lama Penyimpanan terhadap Viabilitas Propagul Rhizophora mucronata - Vonnya Liddyannisa P; Cecep Kusmana; Yulianti Bramasto (Jurnal Silvikultur Tropika, 2011)
The potention of mangrove forests in Indonesia has been decreasing. Therefore, rehabilitation is necessary in order to maintain sustainability of forest ecosystems. One of the efforts is the replanting of mangrove forest. The success of planting depends on the availability of seed. Seeds can not be obtained any time if needed so that storage seed is necessary for seed viability can be maintained within a certain time period until the time of planting arrives. The problem has been arise because of   Rhizophora mucronata is a recalcitrant seed, which is at certain moisture content that relatively high, the propagule tend to be easy to germinate and if the moisture content is low, the propagule will be die or loss of their viability. This study aims to investigate the influence of storage media, storage room and time of storage on propagules viability of R. mucronata and to compare between  the germination from the rapid test (cutting test) and the germination from the direct test.This study used a factorial experiment with completely randomized design (CRD) factorial 5x2x2 with 3 replicates. The details of the factors are: factor A (time of storage) consists of A0 (0 weeks), A1 (1 week), A2 (2 weeks), A3 (3 weeks), and A4 (4 weeks); factor B (storage room) consists of B1 (AC room) and B2 (living room); and factor C (storage media) consists of C1 (sawdust) and C2 (coconut husk).The data collected is the result of cutting test from propagule, the percentage of rooted propagule (PB), moisture content (MC), germination (DB), germination value (NP), the growth rates (KT), shoot and root ratio (NPA). Based on these results, the influence of interaction between storage time, storage room and storage media caused significant differences on germination propagule R. mucronata. The influence of interaction between storage time and storage room caused significant differences to the percent of rooted from propagule R. mucronata. The influence of storage time and storage media caused significant differences in seedling roots to shoot ratio of R. mucronata. In this study, coconut husk media storage that is placed in the air conditioner room capable to maintaining the viability of propagule R. mucronata until the time of storage for 4 weeks. The result of estimation methods viability propagule R. mucronata with cutting test is relatively similar with the directly propagul germination test results.